EVALUATION OF REGIONAL TRAINING CENTER PROGRAM (PUSLATDA) KONI SOUTH SUMATRA PROVINCE TO FACE UPON PON XIX JAWA BARAT - Herri Yusfi (Program Pascasarjana Universitas Negeri Jakarta, 2017)
The purpose of this study was to evaluate context, input, process, and product of Puslatda program in South Sumatra at PON XIX 2016 in West Java. This research was an evaluation research. The subject of research, namely management of KONI south Sumatra, sport branch, trainers, and athletes of sports included in Puslatda program South Sumatra with the amount of 137 people. Data collection techniques used in this study was using interviews, questionnaires, and documentation. Sampling technique used for this study was purposive sampling technique. The data analysis technique used in this study was using qualitative and quantitative descriptive analysis.The result of this study was concluded that the overall result of the evaluation ofPuslatdaprogram in South Sumatra to face upon PON XIX 2016 in West Java is in sufficient category. The explanation of the resultsare: (1) Context evaluation shows good category, clear program planning, presence of goals and objectives in Puslatda program, and vision and mission during Puslatda. (2) the evaluation of inputs is in sufficient category, (3) the evaluation of the process is in sufficient category, the suitability of implementation details of the program and many implementation activities are not in accordance with description of the program tasks; and (4) the evaluation of the products are showing the achievement of the overall Puslatda program is considered in poor category, judged from the achievements of South Sumatra athletes in PON XIX West Java which is not in accordance with the target. Keywords: Program Evaluation, Regional Training Center (PUSLATDA).